PATH55 Characterising orthostatic tremor: a study of 56 patients. Issue 11 (22nd October 2010) - Bain, P; Jones, L
Abstract : Orthostatic tremor (OT) is a rarely reported condition defined as a subjective feeling of unsteadiness on standing, accompanied by a 13- to 18-Hz leg tremor that is relieved during sitting. There are 211 cases in the literature with a 2:1 female preponderance. The commonest presenting complaint being unsteadiness on standing. OT is described as causing tremor of the legs, trunk, and postural arm tremor. The effect of OT on spiral drawing and writing had not been studied. Clonazepam is considered the treatment of choice for OT, which is thought to respond poorly to alcohol. DaTSCAN imaging studies had shown conflicting results. Analysis of our 56 cases confirmed a female preponderance. The age at OT onset distribution had a single peak and was a decade later than essential tremor (ET), which is bimodal. Symptomatic leg tremor was ubiquitous, but OT affected the arms in 50%, head (20%), trunk (16%) and voice and tongue (both 7%) of cases. Tremulous writing and spiral drawings were present in 26.8% and 58.9% of cases respectively; 5.4% of OT cases reported a first degree relative with OT, 5.4% with PD and 10.7% with ET. OT responded to alcohol in 52%. The most effective therapy was primidone; beneficial in 26.7% of cases. Parkinsonian signs were common (37.5% reduced arm swing, 14.3% shuffling gait, 37.5% facial and 8.9% vocal impassivity and 4.3% upper limb rest tremor). DaTSCAN imaging was normal. Our data further characterises the clinical features and therapeutic response of OT.